A Study of Early Neonatal Deaths at Kathmandu Medical College Teaching Hospital - Shrestha, M; Bajracharya, BL; Manandhar, DS (Journal of Nepal Paediatric Society, 2009)
Over 9 million deaths occur each year in the perinatal and neonatal periods globally. 98% of these deaths take place in the developing world. Nepal has a high neonatal mortality rate (NMR) of 38.6 per 1000 live births (2001). Two thirds of the newborn deaths usually occur in the first week of life (early neonatal death). Newborn survival has become an important issue to improve the overall health status and for achieving the millennium developmental goals of a developing country like Nepal. Aims and Objectives: This study was carried out to determine the causes of early neonatal deaths (ENND) at KMCTH in the two-year period from November 2003 to October2005 (Kartik 2060 B.S. to Ashoj 2062). Methodology: This is a prospective study of all the early neonatal deaths in KMCTH during the two-year study period. Details of each early neonatal death were filled in the standard perinatal death audit forms of the Department. Results: Out of the 1517 total births in the two-year period, there were 10 early neonatal deaths (ENND). Early neonatal death rate during the study period was 6.7 per 1000 live births and early neonatal death rate (excluding less than 1 kg) was 6.1 per 1000 live births The important causes of early neonatal deaths were extreme prematurity, birth asphyxia, congenital anomalies and septicaemia. During the study period, there was no survival of babies with a birth weight of less than 1 kg. Among the maternal characteristics, 80% of the mothers of early neonatal deaths were aged between 20-35 years. 50% of the mothers were primigravida. 50% of the mothers of ENNDs had delivered their babies by caesarean section. Discussion: Most of the early neonatal deaths were due to extreme prematurity. Birth asphyxia was the second most important cause of early neonatal deaths. 70% of ENNDs were among LBW babies. Prevention of premature delivery, proper management of very low birth weight babies and early detection and appropriate management of perinatal hypoxia have become important interventional strategies in reducing early neonatal deaths in KMCTH. Conclusion: Early neonatal mortality at KMCTH is fairly low. Good care during pregnancy, labour and after the birth of the baby has helped to achieve these results. Low cost locally made equipments were used to manage the sick newborns. Reduction of early neonatal deaths require more intensive care including use of ventilators, surfactant and parenteral nutrition and prevention of preterm births Key words: Early neonatal death (ENND), neonatal mortality doi:10.3126/jnps.v27i2.1584 J. Nepal Paediatr. Soc. Vol 27(2), p.79-82